The Importance of Law Enforcement and Spatial Planning Regulations Regarding Flood Management - Adikuasa, Muhammad Biyadihie; Riyanto, Hendro Ardiansyah; Putri, Fairus Jelita Regita; Junerosano, Mohamad Bijaksana; Ciptosari, Ciptosari; Aulady, Mohamad F.N (Journal of Civil Engineering, Planning and Design, 2024)
Spatial planning in Indonesia, both national and regional spatial planning, has become a crucial problem that has developed dynamically in recent years. The urgency of spatial management in human life encourages the existence of statutory regulations to address spatial planning. Spatial planning is an important component in determining the success of a region's development, especially in the context of sustainable development. Rapid regional growth, both in urban and rural areas, has had a positive economic impact, but has also given rise to environmental problems, manifested in increasingly critical environmental conditions and the increasing intensity of natural disasters, partly caused by spatial planning violations. One of the significant impacts of spatial planning violations is flooding in Indonesia, which is often caused by land misuse. Therefore, enforcement of spatial planning laws and regulations closely related to flood management is critical. This study uses a qualitative research approach focusing on literature analysis, government policies, and empirical data related to flood management in Indonesia. Empirical data was obtained through interviews with legal experts, spatial planning experts, and related stakeholders. Deductive methods are used in data analysis to identify patterns and relationships between law enforcement, spatial planning regulations, and flood management. The results of this study show that strict law enforcement, clear spatial regulations, and increasing institutional capacity are the keys to reducing flood risk. With synergy between law enforcement and capacity building, potential flood risks can be minimized while building better community involvement and awareness.